Antimicrobial and antioxidant activities of ethanolic extract of fermented black sesame (Sesamum indicum L.) seed dregs - Rosni, Nur Kamariah; Sanny, Maimunah; Rukayadi, Yaya (Journal of Pure and Applied Microbiology, 2024)
Sesame seed dregs or residue refers to the byproduct that is left after sesame seeds have been processed to extract oil and can used in a variety of ways. The residues were subjected to spontaneous fermentation for 7 days at room temperature (23-27°C). The purpose of this research was to analyze antimicrobial and antioxidant activity of ethanolic extract obtained from fermented black sesame seed dregs. The diameter of inhibition zones of extracts against 16 pathogenic microorganisms ranged from 6.88 to 11.00 mm and the minimum inhibitory concentrations ranged from 6.25 to 50.00 mg/mL, with the extract being particularly effective against P. aeruginosa ATCC9027 and C. albicans ATCC10231. Minimum bactericidal/fungicidal concentrations were spread from 25.00 to >50.00 mg/mL. P. aeruginosa ATCC9027 and C. albicans ATCC10231 were completely killed in 2 h incubation time at 4 × MIC in a time-kill kinetics assay. In comparison to raw seeds and seed dregs extracts, the fermented seed dregs extract displayed a higher total phenolic content. In addition, the fermented extract had a lower IC50 concentration compared to raw seeds and seed dregs extracts. These results suggest that fermented black sesame seed dregs can be used as an alternative method to reduce the microorganism's growth. This is crucial for ensuring food safety and minimizing the risk of foodborne poisoning.